OPTIMALISASI BIAYA TRANSPOTASI PENDISTRIBUSIAN TEMPE MENGGUNAKAN METODE LEAST COST (STUDI KASUS: UMKM RUMAH TEMPE) - Julio Alexsander Ap; Elia Mando Wanggai, Marcella Putri Pentury, Tirsa Meirah Pontoh, Heru Sutejo (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
Distribution is an important part of the logistics system that affects operational cost efficiency, especially for Micro, Small, and Medium Enterprises (MSMEs) in the food sector. This study was conducted at the MSME Rumah Tempe Barokah Jaya in Jayapura City, which produces 650 packs of tempeh per day and delivers twice a day: 300 packs in the morning and 350 packs in the evening. The tempeh products are distributed to three destination points: traditional markets, catering businesses, and mobile vendors. The main challenge faced is the high distribution costs, particularly due to the varying distances between destinations. This study aims to minimize total transportation costs using the Least Cost Method. The solution was implemented using Python programming language with the linear optimization library PuLP to determine an efficient shipping allocation based on a cost matrix. The analysis results show that this method can optimally allocate shipments according to the capacity and needs of each destination, thereby minimizing total distribution costs